Improvement of rheological, thermal and functional properties of tapioca starch by using gum arabic. (July 2017) - Singh, Ajaypal; Geveke, David J.; Yadav, Madhav P.
Abstract: Gum arabic (GA) is a fairly inexpensive gum and is well known for its stabilizing, emulsifying, and thickening properties. The effects of adding GA (0.1–1.0%) on solubility, pasting, and rheological properties of 5% native tapioca starch (TS) were analyzed. Dynamic viscoelasticity measurements showed that the elastic modulus (G′) and the viscous modulus (G″) increased in the presence of GA, suggesting a strong interaction between GA-TS in the composite system. All concentrations of GA resulted in higher elasticity (G′ > G″). Pasting properties revealed that the peak viscosity and setback of the TS-GA dispersion decreased with increasing concentration of GA, suggesting the importance of GA in controlling overall viscosity. The flow behavior index (n) decreased from 0.99 to 0.23 as the concentration of GA in the dispersion increased, indicating pseudoplastic behavior (n < 1). However, the consistency coefficient increased by 5 times, from 0.006 to 0.283 Pa.s. with increasing GA concentration (0.1–1.0), showing the synergistic effect of GA. These results show that low concentrations of GA can beneficially improve the rheological behavior of TS. In addition, GA has advantages of being low cost, clean label, and fewer calories, thus broadening the application spectra of native starches. Highlights: Gum arabic can be used to improve functionality of native tapioca starch. Gum arabic has an advantage of being clean label, cheaper, less calorific value. Gum arabic improves functionality of native tapioca starch. Gum arabic and tapioca starch gives highly viscous gels. These gels will open up new avenues of gums in the starch application market.